Answering the Employment Challenge: The Influance of Private Investment, Education, and Population Growth on Labor Absorption in North Luwu Regency - Suprianto, Suprianto; Mustafa, Sri Wahyuny; Qamaruddin, Muh. Yusuf (Equity: Jurnal Ekonomi, 2025)
This study aims to analyze the effect of private investment, education level, and population growth on labor absorption in North Luwu Regency during the period 2010–2024. The method used is a quantitative approach with multiple linear regression analysis, based on secondary data from the Central Statistics Agency (BPS) and DPMPTSP of North Luwu Regency. The results of the study indicate that simultaneously, the three independent variables have a significant effect on labor absorption, as indicated by the F-statistic probability value of 0.001 and the determination coefficient value (adjusted R²) of 0.644. Partially, only the level of education shows a positive and significant effect on labor absorption, with a regression coefficient of 0.139, a t-count value of 3.647, and a significance of 0.004. Meanwhile, private investment has a regression coefficient of 0.021 (t-count = 1.329; sig. = 0.211) and population growth of 0.041 (t-count = 0.189; sig. = 0.728), both of which are insignificant. This finding underscores the importance of improving the quality of education to increase employment opportunities, and highlights that private investment that is not directed to labor-intensive sectors and population growth that is not balanced with job creation can limit labor absorption. The proposed policy implications include formulating incentives for investors in labor-intensive sectors, skills-based vocational education reform, and integrating population and employment policies to ensure that population growth becomes a potential, not a burden on development.